The Influence of Parenting Patterns on Children's Creativity - Astuti, Puji; Nugroho, Putut (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To measure the effect of parenting styles on children's creativity in group B state kindergartens, Muara Bulian district, Batanghari district. Methodology: The type of research used is a type of quantitative research using a posttest group design. The sample used in this study was 133 students. Main Findings: Based on the results of data analysis for parenting pattern data with a sample of 133 children, an average value of 48.79 was obtained, and a standard deviation of 11.29. For data on children's creativity with a sample size of 73, the average deviation is 49.21, the deviation is 9.44. For parenting style Lo (0.0900) < Ltable (0.1036), children's creativity data (0.1015) < Ltable (0.1036). So it can be concluded that both data come from normally distributed populations. Novelty/Originality of this study: This study examines the influence of parental patterns on early childhood creativity.